3D bioprinting and microscale organization of vascularized tissue constructs using collagen‐based bioink. Issue 8 (3rd June 2021) - Muthusamy, Senthilkumar; Kannan, Sathya; Lee, Marcus; Sanjairaj, Vijayavenkataraman; Lu, Wen Feng; Fuh, Jerry Y. H.; Sriram, Gopu; Cao, Tong
Abstract: Bioprinting three‐dimensional (3D) tissue equivalents have progressed tremendously over the last decade. 3D bioprinting is currently being employed to develop larger and more physiologic tissues, and it is of particular interest to generate vasculature in biofabricated tissues to aid better perfusion and transport of nutrition. Having an advantage over manual culture systems by bringing together biological scaffold materials and cells in precise 3D spatial orientation, bioprinting could assist in placing endothelial cells in specific spatial locations within a 3D matrix to promote vessel formation at these predefined areas. Hence, in the present study, we investigated the use of bioprinting to generate tissue‐level capillary‐like networks in biofabricated tissue constructs. First, we developed a bioink using collagen type‐1 supplemented with xanthan gum (XG) as a thickening agent. Using a commercial extrusion‐based multi‐head bioprinter and collagen‐XG bioink, the component cells were spatially assembled, wherein the endothelial cells were bioprinted in a lattice pattern and sandwiched between bioprinted fibroblasts layers. 3D bioprinted constructs thus generated were stable, and maintained structural shape and form. Post‐print culture of the bioprinted tissues resulted in endothelial sprouting and formation of interconnected capillary‐like networks within the lattice pattern and between the fibroblast layers. Bioprinter‐assisted spatial placement of endothelial cells resulted in fabrication of patterned prevascularized constructs that enable potential regenerative applications in the future. Abstract : Bioprinting technology was used to create vascularized tissue constructs with spatially arranged endothelial cells (ECs) and fibroblasts (FBs). CAD (computer‐aided design) software was utilized for the placement of cells in a specific pattern. Constructs thus generated had vessel‐like structures formed along the printed pattern.